FACTORS AFFECT OF THE INDONESIA EXPORT PERFORMANCE FOR COFFEE COMMODITIES 2012-2021 - Andi Killang Pakkanna; Amna Purnama; Andi Ashrafilah Killang; Andi Raisa Aqilah Killang (PT. Arsil Reka Engineering, 2024)
Indonesia is one of the largest coffee-producing and exporting countries in the world. The role of coffee in the Indonesian economy in its position in the world economy illustrates that currently and in the future, coffee commodities have very potential and need to be developed, especially in terms of increasing coffee competitiveness and performance in the international market. Indonesian coffee exports are one of the most in-demand in the world. The quality of Indonesian Robusta coffee is recognized as superior to Vietnamese Robusta coffee. Some Indonesian Robusta coffees can get high marks so they are considered specialty coffees. In addition, the quality of Indonesian Arabica coffee is also recognized as being able to compete with Brazilian Arabica coffee. The purpose of the study was to analyze the effect of tourism, international coffee prices, total coffee production, land area of plantations producing smallholder plantations, and the exchange rate of the rupiah against the US dollar on the export performance of Indonesian coffee commodities. The research method in this study is the Error Correction Model. The research variables used were tourism, international coffee prices, the amount of coffee production, the area of plantations producing smallholder plantations, and the exchange rate of the rupiah against the US dollar which in this study functioned as an independent variable that affected the export performance of Indonesian coffee commodities, which functioned as the dependent variable. The results showed that (1) tourism, international coffee prices, total coffee production, land area of plantations producing smallholder plantations and the exchange rate of the rupiah against the US dollar simultaneously had a significant effect on the export performance of Indonesian coffee commodities, (2) tourism, international coffee prices, the amount of coffee production, land area of plantations producing smallholder plantations partially have a significant and positive effect on the export performance of Indonesian coffee commodities, (3) the exchange rate of the rupiah against the US dollar partially has a significant and negative effect on the export performance of Indonesian coffee commodities.